Partnership of Melon Farmers in Yogyakarta with Startup-Agritech P2P Lending Company, Is It Beneficial? - Hariyani Dwi Anjani; Lestari Rahayu Waluyati (Universitas Muhammadiyah Jember, 2022)
The rapid development of digital technology encourages the agricultural sector to develop so that digital technology-based agritech startup companies are born in the agribusiness sector that provides a platform for financing agricultural businesses and mentoring farmers through a partnership system. This partnership is expected to overcome the main problems often faced by farmers, especially in terms of capital and marketing of agricultural products. This research aims (1) to find out the form and mechanism of farmer partnerships with Startup-Agritech peer to peer (P2P) Lending Company, and (2) to find out the benefits obtained by farmers through implementing partnerships with these companies. This research was conducted in 2020 in the Special Region of Yogyakarta on melon farmers who partnered with a Startup-Agritech of P2P lending company PT. Tani Fund Indonesia. The primary method used is the descriptive method. Types of data collected include primary data and secondary data. Data was collected by interviewing the respondents and collecting secondary data via the internet and relevant literatures. Quantitative and qualitative data were processed using descriptive analysis. The result of the research shows that the partnership is in the form of Agribusiness Operational Cooperation. Farmers can become partners by registering through the company's website with the company's flow and requirements. The benefits obtained by farmers include economic benefits where farmers get easy marketing and certainty of the selling price of their products. Technically, farmers get business capital loans and cultivation assistance. Socially, the partnership increases the motivation of other farmers to join the partnership.